2012
DOI: 10.7763/ijmlc.2012.v2.155
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Approach for Solving Minimum Routing Cost Spanning Tree Problem

Abstract: Abstract-Minimum Routing Cost Spanning Tree (MRCT) is one of spanning tree optimization problems having several applications in network design. In general case, the problem is proved to be NP-hard. The paper uses genetic (GA) approach to solve MRCT problem. Computational experiment results show that GA approach outperforms current approximation algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
1
0
3
Order By: Relevance
“…Một số thuật toán meta-heuristic dạng quần thể đã được áp dụng cho bài toán MRCST như thuật toán di truyền [6,16], thuật toán bầy kiến [12], các thuật toán bầy ong [13,17]. Các thuật toán meta-heuristic dạng quần thể mất nhiều thời gian tìm kiếm hơn so với các meta-heuristic dạng đơn cá thể nhưng khả năng khai phá vùng không gian mới là có thể tốt hơn.…”
Section: Các Thuật Toán Meta-heuristicunclassified
See 2 more Smart Citations
“…Một số thuật toán meta-heuristic dạng quần thể đã được áp dụng cho bài toán MRCST như thuật toán di truyền [6,16], thuật toán bầy kiến [12], các thuật toán bầy ong [13,17]. Các thuật toán meta-heuristic dạng quần thể mất nhiều thời gian tìm kiếm hơn so với các meta-heuristic dạng đơn cá thể nhưng khả năng khai phá vùng không gian mới là có thể tốt hơn.…”
Section: Các Thuật Toán Meta-heuristicunclassified
“…Đoạn mã giả để tạo lời giải ban đầu bởi thuật toán Wong được mô tả như sau: initsolution(G,n,m Kết quả thực nghiệm TABU-MRCST được so sánh với Wong và với các thuật toán meta-heuristic dạng quần thể như MMAS [12], GA [16], ABC [13].…”
Section: Iii3 Tạo Lời Giải Ban đầUunclassified
See 1 more Smart Citation
“…Singh and Sundar (2011) investigated a bee colony algorithm, and Hieu et al (2011) proposed an ant colony algorithm. Genetic algorithm for solving the MRCST problem has been investigated by Tan (2012a) ; Julstrom (2001) and Julstrom (2005) . Julstrom (2005) also coded the tree using Blob code and showed that representing the tree using Blob code in genetic algorithms performed better than coding the tree as an edge-set which was proposed by Raidl and Julstrom (2003) .…”
Section: Introductionmentioning
confidence: 99%